Acidity Constant (pKa) Calculation of Large Solvated Dye Molecules: Evaluation of Two Advanced Molecular Dynamics Methods. Issue 21 (30th September 2016) - De Meyer, Thierry; Ensing, Bernd; Rogge, Sven M. J.; De Clerck, Karen; Meijer, Evert Jan; Van Speybroeck, Veronique
Abstract: pH‐Sensitive dyes are increasingly applied on polymer substrates for the creation of novel sensor materials. Recently, these dye molecules were modified to form a covalent bond with the polymer host. This had a large influence on the pH‐sensitive properties, in particular on the acidity constant (p K a ). Obtaining molecular control over the factors that influence the p K a value is mandatory for the future intelligent design of sensor materials. Herein, we show that advanced molecular dynamics (MD) methods have reached the level at which the p K a values of large solvated dye molecules can be predicted with high accuracy. Two MD methods were used in this work: steered or restrained MD and the insertion/deletion scheme. Both were first calibrated on a set of phenol derivatives and afterwards applied to the dye molecule bromothymol blue. Excellent agreement with experimental values was obtained, which opens perspectives for using these methods for designing dye molecules. Abstract : A little less than neutral : The p K a values of large solvated dye molecules are predicted. Two advanced molecular dynamics (MD) methods are compared and evaluated on a set of phenol derivatives: restrained MD and the insertion/deletion scheme. After evaluation, the insertion/deletion scheme is applied to the solvated dye molecule bromothymol blue, with excellent agreement to experiment.